F' = ma' | = | m |
d -- dt' |
dx' -- dt' |
= | m |
d -- dt' |
d (x-vt) ------- dt' |
(equation 5) |
F' = ma' | = | m |
d -- dt |
d (x-vt) ------- dt |
= |
m |
d -- dt |
d x -- dt |
- | m |
d d (vt) ------- dt dt |
= | m |
d^{2} x ----- dt^{2} |
= | ma | = | F | (equation 6) |
c^{2} | = |
1 --- ε_{0} μ_{0} |
x' | = | x-vt ------------- √(1-v^{2}/c^{2}) |
y' | = | y |
z' | = | z |
t' | = | t - (v/c^{2}).x ------------- √(1-v^{2}/c^{2}) |
(equations 22-25) |
γ | = | 1 ------------- √(1-v^{2}/c^{2}) |
(equation 26) |
x' | = | γ | (x-vt) |
y' | = | y |
z' | = | z |
t' | = | γ | (t - (v/c^{2}).x) |
(equations 27-30) |
(x'_{2} - x'_{1}) | = | γ | (x_{2}-vt) | - | γ | (x_{1}-vt) | = | γ (x_{2} - x_{1}) |